Biological Parameters of False Scad (Decapterus Rhonchus) Encountered in the Coastal Waters of Elmina, Ghana (Research in Agriculture Livestock and Fisheries, 2020)
The study evaluated some population parameters of Decapterus rhonchus in coastal waters of Elmina, Ghana. A total of 210 samples were collected from Elmina landing beach in the Central region of Ghana from July 2019 to December 2019. The total length of individual fish samples was measured and analyzed using TropFish R package. Von Bertalanffy parameters were estimated as asymptotic length (L∞) = 40.6 cm, growth rate (K) = 0.14 per year, and growth performance index (Φ′) =2.367 per year. The length at first capture and maturity were 28.2 cm and 23.2 cm, respectively. Mortality parameters were calculated as total mortality rate (Z) = 1.09 per year, natural mortality rate (M) = 0.29 per year and fishing mortality rate (F) = 0.80 per year. The exploitation rate (E) was 0.73 which suggests that Decapterus rhonchus fishery in coast of Elmina, Ghana is highly overexploited. Reduction of fishing efforts through the removal of subsidies and the introduction of closed fishing season are some of the recommended management measures to sustain the Decapterus rhonchus fishery in Ghana.Res. Agric., Livest. Fish.7(3): 507-515,  December 2020